Muslim mother's rights over the custody of their children / Nur Amin Abdullah and Hanisah Mohd Jali - Abdullah, Nur Amin; Mohd Jali, Hanisah (2006)
This project paper is a study of the rights of Muslim mothers toward the custody of their children in Malaysia. The law that governs this right is Islamic Family Law Act that provides mother as the best person entitled towards the custody of an infant child. However, this right is not absolute. There are various circumstances which deprive this right. Therefore, this project paper is to determine the factors that court will take into consideration in granting custody and to propose relevant recommendations to overcome this matter.